Vulnerabilidade e estabilidade emocional frente ao covid-19: um estudo com discentes da rede básica de ensino em duas cidades dos estados de Sergipe e Pernambuco - Morais, Sidclay Campos de (2023)
In this study, we will discuss the relationship between emotional stability and vulnerability, in a socioecological approach to health, as well as the relationships between this theme and Health Education and Science Teaching. In view of the above, we ask: Does COVID-19 have emotional consequences for students, influencing school performance? Based on this question, in this work we describe and analyze conditions of vulnerability of students to COVID-19, with the aim of mapping sectors of care for Health Education projects. This research presents a qualitative and quantitative approach that identifies itself as an epistemological conception already grounded in the educational field, with the main objective of building knowledge focused on the school restructuring process, in the post-pandemic context. It was organized on two fronts, the first focused on mapping the vulnerable behaviors of basic education students, relating these behaviors to sociodemographic data and emotional profile; the second in a more qualitative way, addressing the inside of schools, as well as analyzing the implementation process of the Life Project discipline, as well as its potential for approaching emotional aspects for student welcoming. The questionnaire had some fundamental assumptions of Socio-Scientific Questions (QSC) and consisted of problem situations with more or less vulnerable response options and the student’s resolutions showed indications of their vulnerabilities. The instrument obtained sociodemographic data and emotional profile, being validated by content analysis following the DELPHI technique, with the participation of judges. A semantic evaluation of the questionnaire was carried out with a sample of students representing the research subjects, and, after the necessary adaptations, we carried out a pilot test with 261 students in the 3rd year of high school, in state schools in Sergipe and Pernambuco. The data produced were processed and statistically analyzed using the Statistical Package for Social Science (SPSS) software, verifying through the Cronbach's Alpha coefficient that the instrument developed showed that quality of life (QoL) has no relation to COVID -19. Qualitative data followed those of Bardin, from the creation of themes both a priori and a posteriori. For correlation analyses, Spearman Rho coefficient was applied, and we did not obtain a significant correlation result. Overall, the results obtained indicated that most students who participated in the pilot study of this research showed that the arrival of a protection method such as the vaccine promotes the idea that we no longer need protection. As if one means of protection canceled out the other. The present study proved to be relevant from a technological point of view, as it proposes to build and validate a performance test capable of measuring indicators of emotional stability, vulnerability and its relationship with quality of life; as it also had scientific and pedagogical relevance, since it sought to correlate quality of life and vulnerability, and although a direct correlation was not found between these variables with the respondent public, an important correlation was perceived between the parent’s education and the use of the vaccine. The data showed that the higher the father education, the greater the student’s adherence to the use of the vaccine, pointing to a direction for educators to work with approaches to prevent COVID-19.